Telemedicine: The Concept and Legal Regulation in Russia, Europe, and USA - Karyagina, Ekaterina Nikolayevna; Sitdikova, Roza Iosifovna (Journal of History Culture and Art Research, 2019)
This article is devoted to a comparative legal analysis of the concept and legal regulation of telemedicine in Russia, Europe (on the example of the EU), and the USA. Telemedicine, the problems of using telemedicine technologies in the provision of medical care are relevant objects of scientific research and discussion both for medicine and law (medical law, civil law). Telemedicine issues have become especially significant in connection with the introduction of Federal Law No. 242-FZ of July 29, 2017 “On Amending Certain Legislative Acts of the Russian Federation on the Use of Information Technologies in the Field of Health Protection”, which legalized the use of telemedicine in Russia. In the framework of this comparative study of the concept of "telemedicine", the article analyzes the definitions of this term, enshrined in the laws of these countries, as well as the definitions available in science and practice. Attention is also being paid to the definition of “telemedicine” given by the World Health Organization. The analysis of the legal regulation of telemedicine considers the relevant sources of legal regulation in Russia, the EU, and the USA, and allows drawing conclusions about the existing problems of legal regulation and gaps in the legislation.